Zirconium Hydroxide‐coated Nanofiber Mats for Nerve Agent Decontamination. Issue 6 (16th February 2017) - Kim, Sohee; Ying, Wu Bin; Jung, Hyunsook; Ryu, Sam Gon; Lee, Bumjae; Lee, Kyung Jin
Abstract: Diverse innovative fabrics with specific functionalities have been developed for requirements such as self‐decontamination of chemical/biological pollutants and toxic nerve agents. In this work, Zr(OH)4 ‐coated nylon‐6, 6 nanofiber mats were fabricated for the decontamination of nerve agents. Nylon‐6, 6 fabric was prepared via the electrospinning process, followed by coating with Zr(OH)4, which was obtained by the hydrolysis of Zr(OBu)4 by a sol–gel reaction on nanofiber surfaces. The reaction conditions were optimized by varying the amounts of Zr(OBu)4, the reaction time, and the temperature of the sol–gel reaction. The composite nanofibers show high decontamination efficiency against diisopropylfluorophosphate, which is a nerve agent analogue, due to its high nucleophilicity that aids in the catalysis of the hydrolysis of the phosphonate ester bonds. Composite nanofiber mats have a large potential and can be applied in specific fields such as military and medical markets. Abstract : Advanced functional fabrics for decontamination of chemical warfare agents have been developed through electrospinning and sol–gel reaction. The composite nanofibers can decompose a nerve agent analogue, diisopropyl fluorophosphate (DFP), and hold great potential in specific fields such as military and medical markets.